Enhancing family health literacy through education on clean and healthy living behaviors in the community - Amelia Putri (Bakti Nusantara Pengabdian Masyarakat Indonesia, 2026)
Background: Family health literacy is a key determinant of clean and healthy living behaviors at the household level; however, many communities still face a gap between health knowledge and daily practice. This gap increases household vulnerability to environment-related health problems and communicable diseases. Objective: This community service program aimed to improve family health literacy and household clean and healthy living behaviors through structured family-based education. Methods: A quasi-experimental one-group pretest–posttest design was applied using a participatory community nursing approach. The intervention was delivered through interactive education sessions, PHBS skill demonstrations, problem-solving discussions, and household mentoring over 6–8 weeks. Measurements were conducted before and after the intervention using a family health literacy questionnaire and a household PHBS observation checklist. Results: The program showed significant improvements in family health literacy scores after the intervention, particularly in understanding health information, assessing household risks, and making preventive health decisions. Household PHBS practices also improved across key indicators, including handwashing with soap, household waste management, routine cleaning of water containers, availability of handwashing facilities, cough/sneeze etiquette, and kitchen and bathroom hygiene. Conclusion: A structured, participatory, and context-based family PHBS education program effectively improves family health literacy and household PHBS practices in the community. The program should be sustained through collaboration among primary health centers, community health volunteers, and local leaders, with periodic mentoring, continuous monitoring, and replication in other communities to broaden public health impact.